An empirical assessment of the effect of corporate international diversification on firm debt and value. (2015) - Olibe, Kingsley O.; Flagg, James C.; Rezaee, Zabihollah
We investigate whether firm's foreign assets and foreign sales are associated with its leverage and excess firm value. Our analysis, of a sample of 200 firms and 1, 037 firm year-observations during the time period of 1998 to 2008, indicates a positive and significant relationship between long-term debt and foreign assets. Our findings also show that long-term debt is negatively related to foreign sales. These findings indicate that international involvement can significantly affect the size of debt in a firm's capital structure. Changes in firm value are positively related to international diversification, indicating that significant gains accrue for shareholders of internationally diversified firms. These results suggest that the mode of a firm's entry into foreign markets has different market implications for shareholders and debt-holders. We also find that significant wealth gains accrue to shareholders of diversified firms with high or medium size debt structure, when taking into consideration of foreign diversification. These results have important implications on how firms design, operate and manage their loan portfolio. Our results are robust regarding the firm's debt and valuation characteristics, and suggest that foreign operations do not destroy firm value.